ĪŚVARA TATTWA: PROLEGOMENA ANTARAREALITASABSOLUTDANPERSONALITIBRAHMAN - Ida Bagus Putu Adnyana; I Gede Suwantana (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2022)
The understanding of Īśvara which is still ambiguous among Hindus makes researchersfeel the need to conduct research on these religion issues. The urgency in this research is toexamine in depth the conception of Īśvara so that it can contribute to Hindus as a whole inunderstanding the concept of Īśvara. This research is a qualitative research with an interpretivedescriptive approach that refers to the Hermeneutic theory. This theory is used because most ofthe discussion in this research seeks to interpret the arguments in the sacred literature to supportthe findings in this research. There are two major discussions in this research, namely related totheconceptof ĪśvaraasabsoluterealityandtheconceptofĪśvaraasthepersonalityofBrahman.The conception of Īśvara in the Brahman perspective as absolute reality means that Īśvara is thesupreme entity itself which does not have any attributes and is not affected by guna or maya. Sothat the quality is in the transcendent esoteric dimension. In contrast to Īśvara as an absolutereality,intheperspectiveofĪśvaraasthepersonalityofBrahmanitisexplainedthatĪśvaraispartof Brahman which is equipped with attributes, tasks, functions, and attributes. So that its levelcannot be equated with Brahman as an absolute reality. This is due to the influence of use andmaya.So itsposition isintheexotericdimensionwhich isimmanent.